Comparative Study between Pioglitazone, Pioglitazone Plus Clomiphene Citrate and Metformine Plus Clomephine Citrate in Treatment of Polycystic Ovarian Syndrome - Mohamed Hassan Mostafa, Osama Mahmoud Azmy, Mohamed Nagi Mohesen, Nesreen Abd-Elfattah Abdallah, Lamiaa Mohamed Alyamany (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Polycystic ovarian syndrome (PCOS) is a prevalent metabolic & reproductive condition in females of reproductive age.Aim and objectives: To assess the effectiveness of Pioglitazone, Pioglitazone plus Clomiphene citrate, Metformin plus Clomiphene citrate in treating infertility in PCOS.Patients & methods: This was a randomized comparative study conducted on patients presented to the Outpatient Clinic of Gynecology of Om-Elmasrieen Hospital, complaining of infertility and diagnosed as having PCOS. Patients were divided into three groups.Results: no significant variances in endometrial thickness, OHSS, and multiple pregnancies between three groups= 0.312, 0.360, 0.635 respectively. However, there were significant differences in drug-related complications, PRL before induction p=0.001, FSH, and Insulin levels p>0.05 before & after induction, but no significant differences in LH or Insulin levels p= 0.759, 0.377 respectively after 6 months.Conclusion:  pioglitazone is as effective as metformin without use of ovulation inducing drug. While metformin cannot be used alone. But it should combine with clomiphene citrate.pioglitazone can be used as an alternative to metformin as a single drug with the least side effects and complications and the same ovulation and pregnancy rates.